Pengaruh Motivasi Kerja dan Budaya Organisasi Terhadap Kinerja Pegawai pada PT. TRANS OCEAN MARITIM - Gilang Yana Abdi; Yogi Yunanto (MES Management Journal, 2026)
This study aims to determine and analyze the influence of work motivation and organizational culture on employee performance at PT Transocean Maritime. The analytical methods applied include multiple linear regression analysis, descriptive analysis, and correlation tests. The results indicate that work motivation has a positive but insignificant effect on employee performance. This condition occurs because the characteristics of the maritime sector place greater emphasis on operational discipline, work systems, and team coordination, meaning that individual motivational drives are not yet the primary factor determining performance. On the other hand, organizational culture is proven to have a positive and significant effect on employee performance. Organizational culture is also found to have a more dominant influence on improving work quality compared to the work motivation variable. Descriptively, employees demonstrate a high level of performance, particularly in terms of efficiency and effectiveness. To achieve more optimal organizational performance, PT Transocean Maritime is recommended to strengthen a professional and collaborative organizational culture, as well as optimize the provision of work facilities that are currently perceived as less than ideal by employees..